Vocabulary Development Strategies in Indonesian Language Learning in Elementary Schools - Damrah Damrah; Muhammad Yani; Ikra Ikra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to identify and evaluate vocabulary development strategies in Indonesian learning in elementary schools. The problem faced is the low mastery of students' vocabulary, which impacts overall language skills. This study uses a descriptive qualitative method with an observation, interview, and documentation approach. The research subjects were grade 2 and grade 5 students in two elementary schools who applied various approaches and learning media, such as crossword puzzles, picture stories, and Whole Language approaches. The results showed that using crossword puzzle media significantly improved students' vocabulary mastery, with an increase in the average score from 65% to 85%. Illustrated stories have also improved vocabulary mastery through a visual approach, which is shown by an increase in the average score from 60% to 80%. In addition, the Whole Language approach has succeeded in improving students' writing skills and vocabulary mastery, with an increase in the average score from 60% to 82%. The application of these strategies not only improves vocabulary mastery but also student motivation and involvement in learning. Based on these findings, it can be concluded that innovative and contextual vocabulary learning strategies effectively improve elementary school students' vocabulary mastery. The use of an integrated approach and relevant media is expected to be applied more widely in the primary education environment. This study recommends the development of technology-based learning media to support vocabulary teaching in the future.